Pengembangan Media Buku Pendamping Sebagai Alternatif Dari Permasalahan Literasi Dini Pada Anak Sekolah Dasar - Made Adi Nugraha Tristaningrat; Komang Trisna Mahartini (STAHN Mpu Kuturan Singaraja, 2021)
This study aims to provide an understanding of the stages of developing companion book media in solving problems that occur in early literacy. Education in the 2013 curriculum requires an integrated thematic concept of education. Integrated thematic learning was chosen because it has the advantage that it can make learning more meaningful. Meaningful learning must also be supported by good and correct media. The most appropriate media at the elementary school level is media that is able to present good visuals and is easily understood by students in the age range of 6-12 years, so that book media can be the choice of companion for the 2013 curriculum. Development of the 2013 curriculum companion book media instrument using the ADDIE Model (Analysis, Design, Development, Implementatian, Evaluation). The stages that will be passed according to the model, among others: at the Analysis stage, an analysis and description of attitude values will be carried out, at the Design stage, a prototype of the book media will be made, at the Development stage the book media will be made as well as the refinement of the book. In the previous prototype, at the Implementation stage, they started using book media to students, while at the Evaluation stage, it was carried out to measure the level of effectiveness of using book media for students.